2022
DOI: 10.1101/2022.09.14.507886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Central metabolism is a key player in E. coli biofilm stimulation by sub-MIC antibiotics

Abstract: Exposure of Escherichia coli to sub-inhibitory antibiotics stimulates biofilm formation through poorly characterized mechanisms. Using a high-throughput Congo Red binding assay to report on biofilm matrix production, we screened ~4000 E. coli K12 deletion mutants for deficiencies in this biofilm stimulation response. Mutants lacking acnA, nuoE, or lpdA failed to respond to sub-MIC novobiocin, implicating central metabolism and aerobic respiration in biofilm stimulation. These genes are members of the ArcA/B re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 141 publications
0
3
0
Order By: Relevance
“…Our previous work on antibiotic-induced biofilm formation in E. coli showed that the response involved changes in NADH redox state and was abrogated by disrupting central metabolism and respiration pathways. 69 Periplasmic disulfide bond formation liberates electrons from free thiols that are shuttled through DsbA and DsbB to respiratory quinones, which then participate in the electron transport chain. 70 Our E. coli biofilm stimulation work also implicated ArcB and NlpE, which are involved in signal transduction and whose activity is regulated by disulfide bonding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous work on antibiotic-induced biofilm formation in E. coli showed that the response involved changes in NADH redox state and was abrogated by disrupting central metabolism and respiration pathways. 69 Periplasmic disulfide bond formation liberates electrons from free thiols that are shuttled through DsbA and DsbB to respiratory quinones, which then participate in the electron transport chain. 70 Our E. coli biofilm stimulation work also implicated ArcB and NlpE, which are involved in signal transduction and whose activity is regulated by disulfide bonding.…”
Section: Discussionmentioning
confidence: 99%
“…71,72 A dsbA mutant of E. coli failed to respond to sub-MIC novobiocin, and narrowly missed our arbitrary hit cutoff for cefixime and tetracycline. 69 Since antibiotics alter respiratory chain flux, 73 and altering respiration activity modulates antibiotic-induced biofilm formation, 69 it is reasonable to speculate that the ability of DsbA/B to cycle electrons to respiratory quinones could also be disrupted by sub-MIC antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation